Studi Pengendalian Motor Listrik di Industri Sebagai Upaya Peningkatan Kualitas Materi Dan Strategi Pembelajaran - Muhammad Alhan; Yaya Finayani (Politeknosains, 2020)
The rapid development of industrial automation technology one technique for controlling the electric motor is very difficult to anticipate by JTE Politama, this will require material adjustments and learning strategies with the development of industrial automation technology to produce graduates according to the needs and the industry can compete in the global world. It required a partnership with the industry to determine the development of industrial automation technology, but it needs to be a partnership with universities that have higher quality and more complete laboratory so it can adopt the course material, equipment / lab module. The result of the adoption of subjects related to electric motors and control techniques organized into 9 RPKPS and teaching materials as well as rewinding machine prototype.